Detection of pseudomonas Contamination in Milk and some dairy products in Diyala Province - Mohamed, Walaa Mahmood (Diyala Journal for Veterinary Sciences, 2023)
Background: Food putrefaction is a critical topic strongly influencing the global require to counteract food instability. Despite the costly use little temperatures, correct preservation for not old dairy yields is constantly endangered on various phases of manufacturing and commercialization via psychotrophic bacteria mostly according to the genus Pseudomonas Aims: To investigate pseudomonas contamination of milk and dairy products Methods: Sixty samples were collected randomly from Diyala province,10 sample for each product. Samples were cultivated to attain non -fermented bacteria on MacConkey agar, and were then tested using the oxidase reagent for confirmation .After that, a sensitivity test was conducted using antibiotic disk to determine their susceptibility . Results : The maximum percentage of isolate was 80% gained from raw milk, 40 % obtained from soft cheese then 20% from each pasteurized milk and salt cheese ,whereas all cream sample not displayed any contamination with pseudomonas . The highest Antimicrobial activity was (30.5 mm)for Meropenem ,(20.5 mm ) for Amikacin ,(18mm)for Gentamycin ,finally 8mm for Erythromycin . Conclusion : The high prevalence of P. aeruginosa was located in raw milk. 2-The highest sensitivity was against Meropenem while the less sensitivity was against Erythromycin. presence of heat stable enzymes produced by Pseudomonas spp., that effect on milk and its products like bad odor, bitter taste, and also affect texture represent another source of contamination additionally to presence viable cells of Pseudomonas spp. . Contamination of milk with prevalence psychrotrophic microbial contamination post pasteurization is consider a latent difficult.